Assessing the Management Strategy and The Potentiality of Fall Armyworm (Spodoptera Frugiperda) Larvae as Poultry Feed - Okello, Emilly Awuor (JOOUST, 2022)
Fall armyworm Spodoptera frugiperda is a serious pest of about 350 plant species such as maize and sorghum. Management of this pest through mass trapping and handpicking of the larvae to feed the chicken would reduce its population. The objectives of the study were; to assess the optimal visual cues of FAW for landing, to evaluate the effectiveness of mass trapping as a method of collecting FAW larvae, to determine the potentiality of FAW larvae as poultry feed. The research assessed optimal visual cues of Spodoptera exigua as a model insect for S. frugiperda. Freshly eclosed moths were tested in a wind tunnel using a water trap with Light emitting diodes (LED). Seven light colours (365, 385, 400, 470, 530, 592 and 650 nm) at one light intensity (brightness) were tested for attractiveness. Data was collected after 30 minutes and 14 hours. To determine the effectiveness of mass trapping FAW, field experiments were done during the long and short rains of 2020 and long rains of 2021. In the long and short rains of 2020, a water trap with UV-A (385 nm) LED light (LWT + UV-A) and a delta trap from Kenya Biologics Company were tested with two categories of pheromones. The pheromones used were S. frugiperda (2001, 2002, 2003, 2004/2005 and 2006) from Pherobank Company and Kenya Biologics pheromone (kbp). LWT was tested with the Pherobank pheromone while the delta trap was tested with Kenya Biologics pheromone. Further, three trap designs, namely: LWT + UV-A (385 nm), the funnel bucket trap from Pherobank, and delta trap, were tested using (2003 and four component (4C)) pheromones. Proximate analysis was performed on air dried samples of fall armyworm larvae and experimental data was compared to secondary data of other chicken feeds. The research found that S. exigua had optimal visual cues at (365, 385, and 400) nm wavelengths compared to (470, 530, 592, and 650) nm wavelengths at (p = 0.01 and p = 0.001). Results for the long rains 2020 showed that LWT + UV-A performed better than the delta trap over three weeks at (p = 0.01, 0.001, and 0.01). Long rains 2021 experiment showed that LWT + UV-A captured higher numbers of FAW moths than the delta and the bucket traps at (p = 0.001). The means of the protein content of FAW larvae (56.22) % was similar to those of BSF larvae (38.41) %, HF larvae (60.94) %, and Soya bean (40.12) %. This research concludes that LWT + UV-A (385nm) has the potential to be utilized for mass trapping S. frugiperda, and FAW larvae have sufficient nutrients to be used as poultry feed. The study recommends that the Ministry of Agriculture and FAO adopt the use of LED water trap in the Integrated Pest Management and also include FAW larvae in poultry diet to boost food security.
Keywords: Poultry Feed; Larvae as Poultry Feed; Fall Armyworm; Larvae; Spodoptera Frugiperda